Knowledge, Practice, and Attitudes of Physicians in Low- and Middle-Income Countries on Fertility and Pregnancy-Related Issues in Young Women With Breast Cancer. (13th January 2022) - Khan, Shah Zeb; Arecco, Luca; Villarreal-Garza, Cynthia; Sirohi, Bhawna; Ponde, Noam F.; Habeeb, Baker; Brandão, Mariana; Azim, Hatem A.; Chowdhury, Arman Reza; Bozovic-Spasojevic, Ivana; Kovalenko, Iryna; Odhiambo, Andrew; et al.
Abstract : PURPOSE: Fertility and pregnancy-related issues are highly relevant for young (≤ 40 years) patients with breast cancer. Limited evidence exists on knowledge, practice, and attitudes of physicians from low- and middle-income countries (LMICs) regarding these issues. METHODS: A 19-item questionnaire adapted from an international survey exploring issues about fertility preservation and pregnancy after breast cancer was sent by e-mail between November 2019 and January 2020 to physicians from LMICs involved in breast cancer care. Descriptive analyses were performed. RESULTS: A total of 288 physicians from Asia, Africa, America, and Europe completed the survey. Median age was 38 years. Responders were mainly medical oncologists (44.4%) working in an academic setting (46.9%). Among responders, 40.2% and 53.8% reported having never consulted the available international guidelines on fertility preservation and pregnancy after breast cancer, respectively. 25.0%, 19.1%, and 24.3% of responders answered to be not at all knowledgeable about embryo, oocyte, or ovarian tissue cryopreservation, respectively; 29.2%, 23.6%, and 31.3% declared that embryo, oocyte, and ovarian tissue cryopreservation were not available in their countries, respectively. 57.6% of responders disagreed or were neutral on the statement that controlled ovarian stimulation can be considered safe in patients with breast cancer. 49.7% and 58.6% of responders agreed or were neutral on the statement that pregnancy in breast cancer survivors may increase the risk of recurrence overall or only in those with hormone receptor–positive disease, respectively. CONCLUSION: This survey showed suboptimal knowledge, practice, and attitudes of physicians from LMICs on fertility preservation and pregnancy after treatment completion in young women with breast cancer. Increasing awareness and education on these aspects are needed to improve adherence to available guidelines and to promote patients' oncofertility counseling. Abstract :